2022
DOI: 10.1039/d2qi00392a
|View full text |Cite
|
Sign up to set email alerts
|

PPy-constructed core–shell structures from MOFs for confining lithium polysulfides

Abstract: For sulfur host materials in Li-S batteries, the structure is important for suppressing the shuttle effect and buffering the volume expansion. A polypyrrole (PPy)-coated core-shell structure is obtained with porous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Moreover, it can be clearly observed that the S 2p spectra in HE‐PBA‐S has an obvious chemical shift compared with that of pristine sulfur (Figure S16), that is from original 165.2 eV to 164.6 eV of S 2p 1/2 and 164.0 eV to 163.4 eV of S 2p 3/2 . This confirms the great interaction between sulfur and HE‐PBA, and the applicability of HE‐PBA as sulfur carriers, which can be fixed in the cathode to suppress the shuttle effect and heighten the cyclic performance for Li−S batteries [28] . By governing the feeding ratio, the sulfur content was controlled precisely, and the accurate amount of sulfur loading was quantitatively analyzed by both thermal‐gravimetric analysis (TGA) (Figure S17) and elemental analysis (Table S2).…”
Section: Resultssupporting
confidence: 62%
“…Moreover, it can be clearly observed that the S 2p spectra in HE‐PBA‐S has an obvious chemical shift compared with that of pristine sulfur (Figure S16), that is from original 165.2 eV to 164.6 eV of S 2p 1/2 and 164.0 eV to 163.4 eV of S 2p 3/2 . This confirms the great interaction between sulfur and HE‐PBA, and the applicability of HE‐PBA as sulfur carriers, which can be fixed in the cathode to suppress the shuttle effect and heighten the cyclic performance for Li−S batteries [28] . By governing the feeding ratio, the sulfur content was controlled precisely, and the accurate amount of sulfur loading was quantitatively analyzed by both thermal‐gravimetric analysis (TGA) (Figure S17) and elemental analysis (Table S2).…”
Section: Resultssupporting
confidence: 62%
“…This confirms the great interaction between sulfur and HE-PBA, and the applicability of HE-PBA as sulfur carriers, which can be fixed in the cathode to suppress the shuttle effect and heighten the cyclic performance for LiÀ S batteries. [28] By governing the feeding ratio, the sulfur content was controlled precisely, and the accurate amount of sulfur loading was quantitatively analyzed by both thermal-gravimetric analysis (TGA) (Figure S17) and elemental analysis (Table S2). Given the high porosity of PBAs, sulfur can be introduced at approximately 70 % by weight.…”
Section: Methodsmentioning
confidence: 99%
“…9 The synthesis of desirable functional materials for the construction of complex MOF composites is highly promising. 10–13…”
Section: Introductionmentioning
confidence: 99%
“…9 The synthesis of desirable functional materials for the construction of complex MOF composites is highly promising. [10][11][12][13] With the increasing demand for efficient energy storage systems, efforts to develop supercapacitors (SCs) with excellent cycling stability, fast charge-discharge processes, and superior power density. 14 Various MOFs are regarded as remarkable potential electrode materials used in SCs due to their low cost and high activity.…”
Section: Introductionmentioning
confidence: 99%